Socioeconomic position early in adolescence and mode of delivery later in life: findings from a portuguese birth cohort - Teixeira, C (2015)
Objective: This study assessed the influence of socioeconomic position at 12 years of age (SEP-12) on the variability in cesarean rates later in life. Methods: As part of the Portuguese Generation XXI birth cohort we evaluated 7358 women with a singleton pregnancy who delivered at five Portuguese public hospitals serving the region of Porto (April/2005–September/2006). Based on the twelve items that described socioeconomic circumstances at age 12, a latent class analysis was used to classify women’s SEP-12 as high, intermediate and low. Multiple Poisson regression was used to estimate adjusted risk ratio (RR) and respective 95% confidence interval (95% CI). Results: The cesarean rates in high, intermediate and low SEP-12 were, respectively, 40.9%, 37.5% and 40.5% (p = 0.100) among primiparous women; 14.2%, 11.6% and 15.5% (p = 0.04) among multiparous women with no previous cesarean and 78.6%, 72.2% and 70.0% (p = 0.08) among women with a previous cesarean. A low to moderate association between SEP-12 and cesarean rates was observed among multiparous women with a previous cesarean, illustrating that women from higher SEP-12 were more likely to have a surgical delivery (RR = 1.12;95%CI:1.01–1.24 comparing high with low SEP-12 and RR = 1.03:95%CI:0.94–1.14 comparing intermediate with low SEP-12) not explained by potential mediating factors. No such association was found either in primiparous or in multiparous women without a previous cesarean. Conclusions: The association between SEP-12 and cesarean rates suggests the effect of past socioeconomic context on the decision concerning the mode of delivery, but only among women who experienced a previous cesarean. Accordingly, it appears that early-life socioeconomic circumstances drive cesarean rates but the effect can be modified by lived experiences concerning childbirth.